PENGARUH GAYA KEPEMIMPINAN KHARISMATIK DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT TOMA KABUPATEN NIAS SELATAN - Junita Tri Anjelika Zebua (Jurnal Ilmiah Mahasiswa Nias Selatan, 2022)
The purpose of this study was to determine the effect of charismatic leadership style and organizational culture on employee performance in the Tomah sub-district office, South Nias Regency. The type of survey used is a causal quantitative type, the data source is employees, and the population and sample of this survey are 35 respondents. The research method is a survey or questionnaire instrument. When several data analysis methods are used, the following is used, namely multiple regression analysis. The results of the investigation show that the Fcount value is 10.271 > Ftable 3.267. From this study it can be concluded that charismatic leadership style and organizational culture influence employee performance in the Tomah District office, South Nias Regency. The research proposals are (1) Leadership in the Tomah District Office is expected to build trust with subordinates and improve employee performance. (2) The leadership of the Tomah sub-district office is expected to pay attention to the work activities of their subordinates/employees. (3) All employees of the Tomah District Office are expected to continue to improve their performance through a certain organizational culture by getting used to following it.